2002
DOI: 10.1016/s0014-5793(02)02244-5
|View full text |Cite
|
Sign up to set email alerts
|

Reversible inhibition of photophosphorylation in chloroplasts by nitric oxide

Abstract: Nitric oxide (NO) is a bioactive molecule involved in diverse physiological functions in plants. Here we demonstrate that NO is capable of regulating the activity of photophosphorylation in chloroplasts. The electron transport activity in photosystem II determined from chlorophyll a fluorescence was inhibited by NO. NO also inhibited light-induced v vpH formation across the thylakoid membrane. High concentrations of nitrite and nitrate did not show such inhibitory effects, suggesting that the inhibition is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
64
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 32 publications
9
64
0
Order By: Relevance
“…Phosphorylation of PSII reaction center proteins D1 and D2, as well as other subunits of PSII, was found to be stimulated by moderately thiol-reducing conditions and kept at a high level also under highly reducing conditions (Carlberg et al, 1999). Furthermore, reversible inhibition of photophosphorylation in chloroplasts by NO was demonstrated (Takahashi and Yamasaki, 2002), suggesting that proteins of the energy transduction system in chloroplast thylakoids could be affected by S-nitrosylation.…”
Section: Discussionmentioning
confidence: 93%
“…Phosphorylation of PSII reaction center proteins D1 and D2, as well as other subunits of PSII, was found to be stimulated by moderately thiol-reducing conditions and kept at a high level also under highly reducing conditions (Carlberg et al, 1999). Furthermore, reversible inhibition of photophosphorylation in chloroplasts by NO was demonstrated (Takahashi and Yamasaki, 2002), suggesting that proteins of the energy transduction system in chloroplast thylakoids could be affected by S-nitrosylation.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that photosynthesis can be affected not only by generation of reactive oxygen species (for review, see Asada, 1999), but also by reaction with NO and other NO-related species. Takahashi and Yamasaki (2002) have shown that NO is capable of inhibiting chloroplast electron transport in a reversible manner. Previously, studies of air pollution had suggested that NO may reduce CO 2 assimilation (Hill and Bennett, 1970).…”
mentioning
confidence: 99%
“…Previously, studies of air pollution had suggested that NO may reduce CO 2 assimilation (Hill and Bennett, 1970). Both photosynthesis and photorespiration have been found to be affected by NO in different plants (Yamasaki, 2000;Takahashi and Yamasaki, 2002). The aim of this work was to identify endogenous sources of NO generation and NO and ONOO 2 -dependent oxidative damage in isolated soybean (Glycine max) chloroplasts.…”
mentioning
confidence: 99%
“…NO is a lipophilic molecule that permeates the membrane and is an important signal molecule in plants growing under biotic and abiotic stresses (Tan et al 2008). NO is reported to induce SG (Beligni and Lamattina 2000), regulate plant metabolism (Leshem et al 1998) and photosynthesis (Takahashi & Yamasaki 2002), and alleviate the effect of oxidative stress (Beligni and Lamattina 1999;. Seed germination was greatly affected by BA with a maximum decrease in BA 3 .…”
Section: Resultsmentioning
confidence: 99%